RANCANG BANGUN KONVEYOR PEMISAH BARANG BERDASARKAN WARNA MENGGUKAN SMART RELAY ZELIO - effendi effendi; Wahyu Priyanto; Akhmad Faruqi (J-Innovation, 2021)
The design of this goods separator conveyor aims to replace human labor in separating goods based on color, where the goods separation system is designed using the zelio smart relay (SR3B261BD) as the main controller, the conveyor belts in this system are driven by motor power wondows and are using a color sensor module. (TCS3200) as a color detection sensor which is then separated by a separation arm designed using a DC motor to separate each item according to the predetermined color, namely red, green and blue. The limit switch is used to limit the separation arm. When the goods have been separated, the separating arm will return to the starting position, this process will continue until the next cycle.